Issues of Improving the Use of Applied Decorative Art in Modern Architecture (In the Case of Urban Planning) (Journal of Architectural Design, 2023)
This article thoroughly covers the issues of using applied decorative art in modern urban planning, their development in our country, scientific research in the fields of architecture and design, improving the use of Applied decorative art, and outlines the prospects for the future.